B KEBIJAKAN KESEHATAN REPRODUKSI BAGI REMAJA MELALUI STANDAR OPERASIONAL PROSEDUR DI DESA BRUDU KABUPATEN JOMBANG - H. Noho, Muhammad Dzikirullah; Fitria, Norma; Islami, Trinah Asi; Muhammad; Akbar, Mochammad Fahd (ABIDUMASY, 2026)
This regency, which has an icon of a city of Islamic boarding school students, was in the spotlight in early 2025 due to the murder and rape of a minor in Sebani Village, Sumobito District. Brudu Village, as a neighboring village, must be responsive to prevent similar incidents from occurring in its village. This response must be addressed by the Brudu Village Government in terms of increasing understanding of reproductive health for adolescents and creating a process for handling problems. The methods used in this community service were carried out through counseling and legal consultations, as well as legal assistance based on the consultation results. The results of this service found that so far the Brudu village community does not understand the law on reproductive health for adolescents, this is indicated by the average 56% of Brudu residents do not know reproductive health for adolescents, especially the process of handling (87%) and rights (56%) regulated in the regulations. The implications of this low understanding, so the community service team provided assistance to the village government and village midwives to establish a standard operating procedure containing a flow of promotive, preventive efforts, and handling of reproductive health problems.